1972
DOI: 10.1063/1.1677050
|View full text |Cite
|
Sign up to set email alerts
|

Electric Deflection of Molecular Beams of the Lanthanide Di- and Trifluorides, ScF3 and YF3

Abstract: Electric-deflection studies on molecular beams of the lanthanide trifluorides have been carried out in the temperature range 1000–1200°C. Substantial refocussing, indicative of polar distortions, has been observed for LaF3, GdF3, and LuF3. Weaker refocussing was present in TmF3. CeF3 and ErF3 showed refocussing barely above the noise level. Defocussing was observed in PrF3, NdF3, TbF3, DyF3, and HoF3. Observations on SmF3, EuF3, and YbF3 were inconclusive due to sample reduction in the oven but showed no refoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 10 publications
3
18
1
1
Order By: Relevance
“…The thermodynamic functions of the gaseous ScX, ScX 2 and ScX 3 molecules, where X = F, Cl, Br and I, were calculated by Krasnov and Danilova (1969) from 298-15-3000°K. Electron deflection studies by Kaiser et al (1972) on ScF 3 (g) indicate that it is very similar to gaseous LaF 3 and YF 3 and probably has a D 2h symmetry.…”
Section: J Halidesmentioning
confidence: 95%
“…The thermodynamic functions of the gaseous ScX, ScX 2 and ScX 3 molecules, where X = F, Cl, Br and I, were calculated by Krasnov and Danilova (1969) from 298-15-3000°K. Electron deflection studies by Kaiser et al (1972) on ScF 3 (g) indicate that it is very similar to gaseous LaF 3 and YF 3 and probably has a D 2h symmetry.…”
Section: J Halidesmentioning
confidence: 95%
“…There is conflicting information in the literature about the shape of these molecules, just as for the transition metal dihalides. ScF 3 was found to be pyramidal by molecular beam deflection, 352 planar by matrix isolation IR, 353 and also planar by quantum chemical calculations. [354][355][356] Chromium trifluoride is planar according to ESR, 357,252b IR, and Raman spectroscopy 255 and a recent quantum chemical calculation, 358 while it is pyramidal by other quantum chemical studies.…”
Section: First-and Second-row Trihalidesmentioning
confidence: 96%
“…359 Most other trihalides are found to be planar, either by spectroscopy or by computation, except YF 3 , which is found to be pyramidal by molecular beam deflection. 352 YCl 3 was reported to be pyramidal by gas-phase IR spectroscopy 360 but planar by computation 361 and by a joint ED/computational study. 362 The computed infrared intensities point to a problem in the deconvolution used for the interpretation of the broad lines in the vapor-phase spectra.…”
Section: First-and Second-row Trihalidesmentioning
confidence: 98%
“…[10,11,12,13,14,15] All calculations so far reported agree in predicting a pyramidal equilibrium structure for the isolated LnF 3 molecules with a very shallow minimum, in agreement with most of the molecularbeam electric deflection data. [16] Recently, we showed that for the LnF 3 ·IG and LnF 3 ·IG 2 (IG = Ne, Ar, Kr, Xe and N 2 ) model complexes, LnF 3 -IG interactions are strong, and a possible LnF 3 planar structure may be found in contrast to the results on isolated molecules. [17,18] Herein, LaF 3 ·Ar n (n = 1-21) van der Waals complexes are proposed as models to account for the argon-matrix effects on the molecular properties of the LaF 3 molecule trapped in solid matrices at cryogenic temperatures.…”
mentioning
confidence: 91%
“…Analogously to group A, the La-Ar eq distances are longer, and the Ar-Ar interactions become the main stabilizing effect. After that, three argon atoms locate on both sides of the LaF 3 molecule with the formation of the LaF 3 ·Ar 16 and LaF 3 ·Ar 19 complexes.…”
mentioning
confidence: 99%